A history of Catalan folk literature - Oriol i Carazo, Carme, 1955-; Samper Prunera, Emili (IVITRA research in linguistics and literature ;, 2019)
"A History of Catalan Folk Literature is the fruit of a collaborative effort between fifteen researchers from various universities and research centres who have joined forces to create a broader study of Catalan folk literature that addresses the Catalan linguistic and cultural territories in their entirety. Since the thirteenth century, Catalan culture has created a rich and abundant literary legacy, and since the mid-nineteenth century this has been complemented by a tradition of folklore studies that remains very much alive today. Within this comparatively recent discipline, folk literature has played a particularly important role. The book presents the evolution of Catalan folk literature studies in each of the areas that make up the Catalan linguistic and cultural territories referred to above. The period considered stretches from the mid-nineteenth century, when the beginnings of a scientific interest in folklore emerged across Europe, to the present day"--